2010
DOI: 10.1159/000318866
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Outside-In and Inside-Out Transobturator Tape Procedures for Stress Urinary Incontinence

Abstract: Aims: This study compared the clinical outcome of patients undergoing outside-in transobturator tape (TOT) or inside-out transobturator tape (TVT-O) procedures for female stress urinary incontinence (SUI). Methods: The study examined the medical records of 615 patients who underwent TOT (376 patients) or TVT-O (239 patients) for SUI, and compared patient characteristics, operation time, duration of hospital stay, cure rates, and complication rates, by conducting a 1-year follow-up survey. Results: The TOT and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
5
0
3
Order By: Relevance
“…The different "inside-out" and "outside-in" TOT methods were found to have equal clinical efficacy and safety, with cure rates between 85.3% and 87.8% [17]. Randomized control trials comparing TOT to retropubic slings supported the new method [18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 93%
“…The different "inside-out" and "outside-in" TOT methods were found to have equal clinical efficacy and safety, with cure rates between 85.3% and 87.8% [17]. Randomized control trials comparing TOT to retropubic slings supported the new method [18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 93%
“…In order to minimize retropubic space injury, TOT has been used to place the sling both with outside-in and inside-out approachesas proposed by Delorm [10] [18] and by Leval [2]. Many retrospective studies have shown that the difference between inside-out TOT and outside-in TOT approaches was insignificant [19]. The authors concluded that both of these approaches were equally safe and clinically effective.…”
Section: Discussionmentioning
confidence: 99%
“…9,261 In addition, the qualifiers persistent or de novo 261 were often used. De novo OAB, indicating the occurrence of OAB after sling surgery, was reported in 0-48% of patients in various studies (REFS 17,18,20,26,39,(46)(47)(48)(50)(51)(52)(53)55,(57)(58)(59)61,62,66,67,70,(73)(74)(75)(76)(77)79,83,87,88,91,92,96,97,99,140,152,153,155,157,159,161,163,164,(166)(167)(168)(170)(171)…”
Section: Oab Symptomsmentioning
confidence: 99%
“…Compression from the sling is by far the most common cause of urethral obstruction, and at least one case of urethral stricture accompanied by urethral erosion has been reported. 9 The incidence of urethral obstruction requiring surgical intervention ranges from 0% to 8.9% in patients fitted with RP slings and from 0% to 21.3% for those with TOT slings (REFS 17,18,20,21,23,26,30,(46)(47)(48)(50)(51)(52)(53)(54)(55)(56)58,59,(61)(62)(63)(64)(66)(67)(68)(69)71,74,77,(80)(81)(82)(83)(86)(87)(88)(89)(90)(91)(92)(97)(98)(99)148,159,163,166,…”
Section: Oab Symptomsmentioning
confidence: 99%
See 1 more Smart Citation